First record of the invasive species Parasaissetia nigra in Greece - Tsagkarakis, A. E.; Ben-Dov, Y.; Papadoulis, G. Th. (ENTOMOLOGIA HELLENICA, 2016)
In June 2014, the nigra scale Parasaissetia nigra (Nietner) (Hemiptera: Coccidae) was recorded for the first time in Greece on pomegranate, Punica granatum. Its occurrence was observed in an ornamental pomegranate tree in the campus of the Agricultural University of Athens. Information on its morphology, biology and distribution is presented.